Fogwater deposition of radiocesium in the forested mountains of East Japan during the Fukushima Daiichi Nuclear Power Plant accident: A key process in regional radioactive contamination. (1st March 2020) - Imamura, Naohiro; Katata, Genki; Kajino, Mizuo; Kobayashi, Masahiro; Itoh, Yuko; Akama, Akio
Abstract: Because of limited environmental monitoring data, the regional-scale impact of the deposition of fogwater radiologically contaminated by the Fukushima Daiichi Nuclear Power Plant (F1NPP) accident remains unclear. To redress this situation, we present an observational report of the radiocesium concentration in fogwater and its deposition in a Japanese forest during the early stages of the F1NPP accident (March 2011). The data were acquired by using a passive collector to capture fogwater above the forest canopy on a monthly basis. In addition, the radiocesium concentrations in monthly throughfall and stemflow were measured under the canopies of four tree species. The 137 Cs activity concentration in fogwater during the observational period was 45.8 Bq L −1, which was twice as high as that present in bulk precipitation. The ratio of 137 Cs in throughfall to that in bulk precipitation (TF/BP ratio) ranged from 1.0 to 2.5. The high TF/BP ratios may have been caused by the high radiocesium concentration in fogwater deposition. Based on this assumption, we assessed the TF/BP ratio according to the 137 Cs activity concentrations of throughfall and bulk precipitation measured in various mountainous regions in East Japan. Our results reveal that the TF/BP ratio is high at some sites and that it increases with elevation. Sites with a high TF/BP ratio were almost entirely situated in areas of fogwater deposition, as predicted by an atmospheric dispersion model. In addition, sites with a high TF/BP ratio were above the cloud base at the time when plumes with high atmospheric 137 Cs activity concentrations passed through the areas. Thus, these measurements of radiocesium in fogwater during the early stages of the F1NPP accident provide evidence that fogwater with high radioactive contamination was deposited in the forested mountain areas of East Japan. Given the major impact of fogwater deposition of radiocesium, its role should be considered carefully to better understand radiocesium cycling in forest ecosystems. Highlights: High concentrations of 137 Cs activity in throughfall were most likely due to fogwater deposition. Forested mountain areas were contaminated by fogwater deposition in East Japan. Fogwater deposition may have a role in radiocesium cycling in forest ecosystems.